2020
DOI: 10.1177/0300060520924546
|View full text |Cite
|
Sign up to set email alerts
|

A simple and effective method for bladder blood clot evacuation using hydrogen peroxide

Abstract: Objective Urinary retention caused by bladder clots can be frustrating because such blood clots are difficult to remove. We established a novel technique in which hydrogen peroxide is applied to evacuate bladder clots. Methods In this single-center retrospective study, we evaluated 31 patients with retention of blood clots in the bladder who underwent emergency evacuation using hydrogen peroxide. Results The patients comprised 17 men and 14 women with mean age of 61.2 years (range, 42–82 years). Hydrogen perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…Although MBW is the standard procedure for urinary retention by blood clot formation, the most efficient catheter for MBW has not yet been studied. MBW is sometimes time-consuming, exhausting, and inefficient, which might prolong the patients’ suffering 2 . CATCH-22, a standardized MBW protocol for the management of bladder clot retention, recommended the use of at least 22 Fr catheters, the best infection control catheter manipulation, to assist clearing clot in all quadrants of the bladder, and Clot + 1 L rule 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although MBW is the standard procedure for urinary retention by blood clot formation, the most efficient catheter for MBW has not yet been studied. MBW is sometimes time-consuming, exhausting, and inefficient, which might prolong the patients’ suffering 2 . CATCH-22, a standardized MBW protocol for the management of bladder clot retention, recommended the use of at least 22 Fr catheters, the best infection control catheter manipulation, to assist clearing clot in all quadrants of the bladder, and Clot + 1 L rule 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, it causes urinary retention by blood clot formation, which is a common emergency in urological practice. Patients may develop severe pain if the clots are not evacuated in a timely manner 2 . Blood clot retention can develop various symptoms, including tachycardia, hypertension, bladder rupture, and perforation from an acutely overdistended bladder 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important effect that hydrogen peroxide cause is hemostasis due to the activation of the tissue factor, platelet aggregation regulating the contractility and function of the barrier of the endothelial cells and by stimulating the activation of the platelet-derived growth factor [ 6 , 8 ]. Several articles demonstrated that there were no adverse effects with the use of hydrogen peroxide in the bladder [ 2 , 9 , 10 ]. The concentration used in this study was the one proposed by Warlick et al.…”
mentioning
confidence: 99%
“…There could be a big concern in what are the potential damages to the bladder mucosa; nevertheless, Xu et al. [ 9 ] mentioned that in cystoscopy performed 6 months posterior to the bladder irrigation with hydrogen peroxide no abnormalities were found.
Figure 1 The placement of the three-way catheter and bladder flushing.
…”
mentioning
confidence: 99%